Simultaneous bilateral vision loss after total hip arthroplasty: what an orthopedic surgeon has to worry about - Focaccia, Marco; Cevolani, Luca; Staals, Eric Loedewijk; Necci, Fabiana; Alì, Nikolin (Lo Scalpello - Journal, 2024)
Introduction. Perioperative visual loss (POVL) is a rare and unpredictable complication of non-ocular surgical procedures. Case report. Here we report a case of visual loss after a routine orthopedic procedure. After a surgical procedure of total hip arthroplasty, sudden visual loss was referred by the patient and anterior ischemic neuropathy was diagnosed. Despite treatment, the patient has not regained his sight after more than a year. Discussion. Multiple studies have tried to identify pre-existing conditions or intra-operative factors that may contribute to ischemic optic neuropathy. Age, sex, intraoperative anemia, and acute blood loss seems to predispose patients to POVL, even if no cut-off values have been defined. Preoperative anemia and peripheral vascular disease may be risk factors for this condition. Prone position and prolonged operative time are intraoperative risk factors. However, the development of POVL remains unpredictable and a multi-factorial etiology seems to be the most plausible explanation. Conclusions. POVL is a rare and unpredictable complication that can occur in patients of all ages, even in routine uncomplicated orthopedic procedures. Pathogenesis and etiology are still to be defined and no preventive or treatment guidelines had been established.